HUBUNGAN ANTARA TEKNIK MENGANGKAT BEBAN DENGAN KELUHAN NYERI PINGGANG PADA BURUH GENDONG DI PASAR BUAH JOHAR SEMARANG 2012 - MG Catur Yuantari; Rina Maylina Fitriani (Dian Nuswantoro Semarang, 2012)
Background Lifting technique is a way to lift the loads with a shoulder and the loads are in appropriate capacity. Haul labors in 2nd floor of Yaik Permai in Johar fruits market in Semarangare informal workers who work manually in lifting goods using shawl and did not use other equipments so there would be risks of accident on workers such as aches or injuries to the lower back. The purpose of this research is to figuring out correlation between lifting technique and complaints of lower back pain on haul labor in Yaik Permai in Johar fruits market in Semarang 2012.Method: This research is an Explanatory Research with survey method and Cross Sectional study design. The populations of this research are 62 haul labors 2nd floor of Yaik Permai in Johar fruits market in Semarang. The samples are 27 haul labors that taken by using Purposive Sampling, with inclusion criteria aged 27-40 years old, 1-year service, female, and exclusion criteria did not have lower back pain record before, in a healthy condition during the data collection, and there is a history of sprains prior to working.Result: The study showed that 88,9% haul labors had complaints of lower back pain while working, 77,8% experiencing lower back pain due to lifting jobs, 70,4% experiencing pain when returning home, 59,1% sprained on hip area while working, 70,4% transporting on over the knees bellow the shoulders and close to the body, 88,9% who put their body closer between two legs if the loads are on the floor. There is correlation between lifting technique and complaints of lower back pain with p value 0,012 and correlation coeficiency (r) 0,479 which indicates that there is a significant correlation.Conclusion:Therefore, it is suggested to haul labors to do the lifting jobs correctly, in accordance with lifting techniques and using tools to reduce the heavy burden such as cart orstroller.Keywords : Lifting Technique, Complaints of Lower Back Pain, Haul Labors